SISTEM INFORMASI EKSEKUTIF SEBAGAI PENDUKUNG PENGANGGARAN DI PEMERINTAH DESA MELALUI INTEGRASI SISTEM DENGAN TEKNOLOGI WEB SERVICE DAN APLIKASI SELULER (STUDI KASUS DESA DERMAJI) - Trias Bratakusuma; Zanuar Rifai (UPPM Akademi Komunitas Semen Indonesia, 2019)
The usage of informatics in this case was e-governement in the government which was included in presidential instructions No.3 2003 was already implemi through regional e-governement that was adjusted based off of local resources and regional needs. The importance of e-governement was affected by at least 3 factor: electronic communication between public sector and society offering both of them a new way to participate and interact. The cyber room in public service makes the deletion of bureaucracy structure and the classic process in E-governement community can improve the service and also offers information on a local level. Even though the dermaji village government has implemented the e-governement but there's more to delete the old bureaucracy system that was old and complicated. Executive informatics is one of the type of informatics for executive that was used to facilitate informatics need in order to reach the goal of an organization. In the implementation this technology was often time utilized by the Village government for main source of information in supporting decision making, particularly when arranging a weak budget in terms of mechanism and supporting data source. With this system we hope that the decision making in budget arrangement became more objective. The development method in this system was scrum.